The Creative Visual Analysis : Postmodern Visual Communication in the Black Hawk Down Headline Article on Jawa Pos - Sukirno, Zakaria Lantang; Irfan, Edoardo; Alma Mandjusri, Alma; Setyowati Karyaningtyas, Setyowati (Rumah Jurnal, University of Jember, 2025)
Jawa Pos, on Saturday, February 1, 2025, published an article headlined